The Diasystematic Status of the Diatopic Axis - Schøsler, Lene (Scandinavian Studies in Language, 2023)
This paper is anchored in the tradition of variationist linguistics of Germanic and Romance studies in Europe. In variationist linguistics, the dimension of ‘space’ is essential. According to Flydal (1952:245) this dimension is one of the “extrastructuralismes” which, together with the structures of language, forms the “architecture de langue”. The other important extrastructural dimension mentioned by Flydal is diastratic, i.e. social variation. Coseriu takes over these two notions from Flydal, adding a third dimension: the diaphasic variation (1969:148 ss.). A fourth dimension proposed by Koch & Oesterreicher (1990), opposing the spoken vs written conception, implying the distinction between communicative immediacy or distance (the diamesic variation), was, however, not included by Coseriu. A number of publications and articles have recently questioned the theoretical basis of the three or four dimensions taken over from Flydal by Coseriu and further elaborated in the tradition of variationist linguistics in Romance and Germanic studies. My contribution focuses on the diatopic level, but intends to show, by means of a number of case studies, that this level cannot be considered independently of other variation factors.